A kinase‐dead version of FERONIA receptor‐like kinase has dose‐dependent impacts on rosette morphology and RALF1‐mediated stomatal movements. Issue 20 (24th September 2018) - Chakravorty, David; Yu, Yunqing; Assmann, Sarah M.
Abstract : The receptor‐like kinase FERONIA (FER) pleiotropically affects plant reproduction, development, and stress tolerance. We recently showed that the FER ligand RALF1 promotes stomatal closure and inhibits stomatal opening in a G‐protein‐dependent manner. FER responses have been designated as kinase‐dependent or kinase‐independent, based largely on fer complementation assays employing a kinase‐dead FERK565R. Our quantification of FERK565R‐GFP transcript and FERK565R‐GFP protein in fer complementation lines reveal that, even within individual complementation lines, different levels of FERK565R expression prevail. FERK565R‐GFP expression comparable to that of FER in Col‐0 plants fail to elicit complementation of either fer rosette phenotypes or RALF1‐elicited stomatal movements, whereas overexpression levels of FERK565R‐GFP result in complementation. These results suggest possible alternative interpretations of previous conclusions regarding kinase‐independent FER signaling. Abstract :